Psychosocial factors of binge-eating: a meta-analytical study - A. A. Lifintseva; U. U. Novikova; T. A. Karavaeva; M. V. Fomicheva (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The results of meta-analysis of constitutional-biological, personal, microsocial and somatogenic factors of binge-eating are discussed in this paper. The meta-analysis involved 38 studies published in English language between 2000 and 2016. The random effects model was chosen for meta-analysis and the following methods were used: Pearson correlation coefficient (r) and Fisher’s Z-test. As additional procedures, an I2- test was conducted to assess the homogeneity of the studies, a publication bias analysis to level the error of unpublished data, and a «trim-and-fill» test. As a result of the meta-analysis, the leading psychosocial factors, influencing the formation and development of compulsive overeating were identified — these are depressive symptoms, negative affect, perception of body image, stress and personal predictors (anxiety, temper, impulsiveness, reduced level of emotional intelligence, psychological rigidity). However, no significant gender differences were found.